2014
DOI: 10.2478/s11532-014-0532-4
|View full text |Cite
|
Sign up to set email alerts
|

Microwave assisted extraction of essential oils from enzymatically pretreated lavender (Lavandula angustifolia Miller)

Abstract: In this study, microwave assisted a hydrodistillation process (MWHD) of essential oils from lavender (Lavandula angustifolia Miller) was investigated. In order to examine any potential differences in essential oil extraction, the lavender flowers underwent enzymatic pretreatment.A 23 factorial design of experiments, combined with statistical methods of data analysis were used to optimize enzymatic pretreatment and to evaluate the influence of major variables (enzyme concentration, temperature and pH) on the pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Such coarse approach involves the use of hydrolytic enzymes to disrupt the cell walls, predominantly composed by highly complex large polymers such as cellulose, hemicellulose, lignin and pectin. The EAE has been successfully used to enhance the recovery of polyphenols from blackcurrant (Landbo and Mayer, 2001) citrus peel (Li et al, 2006) and ginger (Chari et al, 2013); lycopene from tomato (Zuorro et al, 2011); oil from Forsythia suspens (Gai et al, 2013); protein from olive leaves (Vergara-Barberán et al, 2015); starch from potato (Ramasamy et al, 2014) and essential oils from garlic (Sowbhagya et al, 2009), celery seeds (Sowbhagya et al, 2010), cumin (Sowbhagya et al, 2011), thyme and rosemary (Hosni et al, 2013) and lavender (Calinescu et al, 2014). Although the enzymeassisted approach has largely improved the extraction yield of bioactive compounds of the aforementioned species, there are no reports on the application of this procedure on bay leaves.…”
Section: Introductionmentioning
confidence: 98%
“…Such coarse approach involves the use of hydrolytic enzymes to disrupt the cell walls, predominantly composed by highly complex large polymers such as cellulose, hemicellulose, lignin and pectin. The EAE has been successfully used to enhance the recovery of polyphenols from blackcurrant (Landbo and Mayer, 2001) citrus peel (Li et al, 2006) and ginger (Chari et al, 2013); lycopene from tomato (Zuorro et al, 2011); oil from Forsythia suspens (Gai et al, 2013); protein from olive leaves (Vergara-Barberán et al, 2015); starch from potato (Ramasamy et al, 2014) and essential oils from garlic (Sowbhagya et al, 2009), celery seeds (Sowbhagya et al, 2010), cumin (Sowbhagya et al, 2011), thyme and rosemary (Hosni et al, 2013) and lavender (Calinescu et al, 2014). Although the enzymeassisted approach has largely improved the extraction yield of bioactive compounds of the aforementioned species, there are no reports on the application of this procedure on bay leaves.…”
Section: Introductionmentioning
confidence: 98%
“…Boelens (2017) reported that aldehydes (cuminaldehyde) present in cumin essential oil as volatile compounds are responsible for cumin seeds' characteristic flavor. Different assisted methods for hydrodistillation to extract cumin essential oil such as ultrasound‐assisted extraction (Allaf, Tomao, Ruiz, & Chemat, 2013; Sereshti, Rohanifar, Bakhtiari, & Samadi, 2012), microwave heating (Behera et al, 2004; Calinescu et al, 2014), enzyme assisted extraction (Chávez‐González, López‐López, Rodríguez‐Herrera, Contreras‐Esquivel, & Aguilar, 2016; Sowbhagya, Srinivas, Purnima, & Krishnamurthy, 2011), green extraction (Djermane et al, 2019), ohmic‐assisted hydrodistillation (Gavahian et al, 2017), supercritical CO 2 extraction (Goodarznia & Eikani, 1998; Guan, Li, Yan, Tang, & Quan, 2007; Saxena et al, 2015), and non‐thermal cold plasma (Pragna, Ranjitha Gracy, Mahendran, & Anandharamakrishnan, 2019) have been used earlier. The impact of plasma bubbling on extraction yield and cuminaldehyde content of cumin essential oil are estimated in this study.…”
Section: Introductionmentioning
confidence: 99%
“…The ginger essential oil was obtained through a microwave assisted hydrodistillation process, using an optimized procedure similar to the literature [27]. The plant material used was fresh shredded ginger root.…”
Section: Mahd -Multimode Cavitymentioning
confidence: 99%